2010
DOI: 10.1089/neu.2009.1211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Co-Administration of Clenbuterol and Testosterone Propionate on Skeletal Muscle in Paraplegic Mice

Abstract: Spinal cord injury (SCI) is generally associated with a rapid and significant decrease in muscle mass and corresponding changes in skeletal muscle properties. Although beta(2)-adrenergic and androgen receptor agonists are anabolic substances clearly shown to prevent or reverse muscle wasting in some pathological conditions, their effects in SCI patients remain largely unknown. Here we studied the effects of clenbuterol and testosterone propionate administered separately or in combination on skeletal muscle pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“…In that study, fiber size was reduced by 49% by SCI for gastrocnemius, soleus, and tibialis anterior, whereas only a 30% reduction in CSA was observed for muscle fibers in SCI animals administered testosterone Thus, the findings indicated that testosterone protected against 40% of the loss that would have otherwise occurred. Testosterone was also found to increase body weight and muscle fiber CSA of the soleus and extensor digitorum longus muscles in male mice at 4 and 8 weeks after SCI (Ung et al, 2010). Of note, the mass of these muscles was not significantly altered by this agent.…”
Section: Muscle Mass and Proteinmentioning
confidence: 80%
See 1 more Smart Citation
“…In that study, fiber size was reduced by 49% by SCI for gastrocnemius, soleus, and tibialis anterior, whereas only a 30% reduction in CSA was observed for muscle fibers in SCI animals administered testosterone Thus, the findings indicated that testosterone protected against 40% of the loss that would have otherwise occurred. Testosterone was also found to increase body weight and muscle fiber CSA of the soleus and extensor digitorum longus muscles in male mice at 4 and 8 weeks after SCI (Ung et al, 2010). Of note, the mass of these muscles was not significantly altered by this agent.…”
Section: Muscle Mass and Proteinmentioning
confidence: 80%
“…The administration of testosterone to spinal cord-transected rats or mice reduced muscle atrophy as assessed by myofiber cross-sectional area (Gregory et al, 2003;Ung et al, 2010). The specific mechanisms behind this benefit are uncertain.…”
mentioning
confidence: 99%
“…In this respect, results achieved by using testosterone replacement therapy both in animal research (5) and human studies (3) have been promising. To date, no studies have been focused on improving testosterone levels by performing an intervention program based on regular exercise in individuals with chronic SCI.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that clenbuterol alone can partially increase muscle mass and size in Tx mice. 18 We now show that clenbuterol treatment combined with BCD-induced training increases muscle mass, whole muscle CSA, and single-fiber CSA values. In fact, those values were similar to those in non-Tx Figure 3.…”
Section: Pharmacological Activation Of the Cpg In Nonassisted Paraplementioning
confidence: 52%
“…Clenbuterol was chosen for this study based on promising muscle-building effects already shown in models of muscle wasting as well as in paraplegic mice. [14][15][16][17][18] …”
Section: Introductionmentioning
confidence: 99%